Recurrent sustained atrial arrhythmias and thromboembolism in Fontan patients with total cavopulmonary connection. (April 2021) - Egbe, Alexander C.; Miranda, William R.; Devara, Janaki; Shaik, Likhita; Iftikhar, Momina; Goda Sakr, Ahmed; John, Anitha; Cedars, Ari; Rodriguez, Fred; Moore, Jeremy P.; Russell, Matthew; Grewal, Jasmine; et al.
Abstract: Background: Total cavopulmonary connection (TCPC) is associated with a lower risk of incident atrial arrhythmias as compared to atriopulmonary Fontan, but the risk of recurrent atrial arrhythmias is unknown in this population. The purpose of this study was to determine the incidence and risk factors for recurrent atrial arrhythmias and thromboembolic complications in patients with TCPC. Methods: This is a retrospective multicenter study conducted by the Alliance for Adult Research in Congenital Cardiology (AARCC), 2000–2018. The inclusion criteria were TCPC patients (age > 15 years) with prior history of atrial arrhythmia. Results: A total of 103 patients (age 26 ± 7 years; male 58 [56%]) met inclusion criteria. The mean age at initial arrhythmia diagnosis was 13 ± 5 years, and atrial arrhythmias were classified as atrial flutter/tachycardia in 85 (83%) and atrial fibrillation in 18 (17%). The median duration of follow-up from the first episode of atrial arrhythmia was 14.9 (12.1–17.3) years, and during this period 64 (62%) patients had recurrent atrial arrhythmias (atrial flutter/tachycardia 51 [80%] and atrial fibrillation 13 [20%]) with annual incidence of 4.4%. Older age was a risk factor for arrhythmia recurrence while the use of a class III anti-arrhythmic drug was associated with a lower risk of recurrent arrhythmias. The incidence of thromboembolic complication was 0.6% per year, and the cumulative incidence was 4% and 7% at 5 and 10 years respectively from the time of first atrial arrhythmia diagnosis. There were no identifiable risk factors for thromboembolic complications in this cohort. Conclusions: Although TCPC provides superior flow dynamics and lower risk of incident atrial arrhythmias, there is a significant risk of recurrent arrhythmias among TCPC patients with a prior history of atrial arrhythmias. These patients may require more intensive arrhythmia surveillance as compared to other TCPC patients.